Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Menjadi Guru Tetap Yayasan Menggunakan Metode Simple Additive Weighting (Studi Kasus Yayasan Pendidikan Islam Assa Adah Tajurhalang) - Muhamad Fikri; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Commonly carried out in schools, especially at the Assa Adah Islamic Education Foundation. Assessment, evaluation and awarding are carried out aimed at spurring the performance of teachers in the teaching and learning process so as to improve teacher achievement, the assessment is carried out to obtain honorary teachers who will be appointed as permanent teachers at this time. In practice, discrepancies often occur in terms of determining the results of the selection of prospective teachers for permanent foundations because each criterion does not have an assessment weight. In addition, the process of data collection and report generation is still done manually. So it is less effective and allows data loss. To determine recommendations and minimize discrepancies in values in determining the results of prospective permanent teachers of the foundation, the Simple Additive Weighting method can be used, this method is a method in multiattribute decision making, in this study the Simple Additive Weighting method is used for the process of weighting the criteria and the ranking process of honorary teachers whose achievements with predetermined criteria. The results of this study produce a ranking report of prospective teachers who have good performance who have been selected, and the output of the application can assist decision makers in choosing alternatives to appointing permanent teachers to the foundation. The application in this research is implemented using the PHP programming language and the database using Mysql.